Association between Staphylococcus aureus Exfoliative Toxins and Staphylococcal Scalded Skin Syndrome: A Systematic Review - Risca Hijrianti; Rizky Arianto Nugroho (International Medical Journal Corp. Ltd, 2025)
Introduction: Staphylococcal Scalded Skin Syndrome (SSSS) is a severe, toxin-mediated dermatosis caused by specific strains of Staphylococcus aureus. While the causal link to exfoliative toxins (ETs) is well-established, a systematic synthesis correlating specific toxin types (ETA, ETB) with the full spectrum of clinical outcomes, microbiological profiles, and prognostic indicators is lacking. This review aims to systematically analyze and synthesize the evidence on the association between S. aureus ETs and the clinical, microbiological, and prognostic features of SSSS, providing a comprehensive evidence base for clinical practice (Ladhani, 1999; Mishra, Yadav and Mishra, 2016). Methods: Following the PRISMA 2020 guidelines, a systematic search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library was conducted for observational studies and case series (n≥5) reporting on SSSS patients with confirmed S. aureus infection and identified toxin types (ETA/ETB). Two independent reviewers performed study selection, data extraction, and a rigorous quality appraisal using the ROBINS-I tool for non-randomized studies. A narrative synthesis of over 15 distinct outcomes was performed, with a primary focus on stratifying data by the causative toxin profile to elucidate differential effects (Page et al., 2021). Results: A total of 17 studies, comprising 1,027 patients, met the inclusion criteria. The evidence strongly indicates a significant dichotomy in clinical presentation based on toxin type. ETA was predominantly associated with localized disease (bullous impetigo), whereas ETB was significantly correlated with the more severe, generalized form of SSSS (p<0.001) (Bukowski et al., 2005). Pediatric populations (<6 years) were primarily affected, with mortality rates consistently below 5% in this group (Handler and Schwartz, 2021). In stark contrast, adults with comorbidities, particularly renal failure and immunosuppression, exhibited markedly high mortality rates exceeding 50% (Ladhani, 2003). The prevalence of methicillin-resistant S. aureus (MRSA) varied significantly by geographic region, with some Asian countries reporting MRSA in over 90% of SSSS cases, necessitating a region-specific approach to empirical therapy (Lee et al., 2021). Complications such as dehydration, electrolyte imbalance, and secondary sepsis were common in generalized disease, though healing was typically rapid and without scarring due to the superficial nature of epidermal cleavage (Oakley, 2017). Discussion: The findings strongly support a host-pathogen interaction model where the clinical phenotype of SSSS is determined not only by the toxin but critically by the host's specific immune status. Lower population-level antibody titers against ETB likely permit its systemic dissemination, leading to generalized disease, whereas higher anti-ETA antibody prevalence contains the infection locally (Bukowski et al., 2005). This has significant implications for diagnosis, where differentiation from Toxic Epidermal Necrolysis (TEN) is paramount, and for management, which necessitates a geographically informed approach to empirical antibiotic selection to address the dramatic regional variations in MRSA prevalence (Popescu et al., 2018; Lee et al., 2021). Conclusion: S. aureus exfoliative toxins are definitively and causally associated with SSSS. The specific toxin serotype, particularly ETB, is a significant predictor of the clinical phenotype and severity, an association that is critically modulated by host immunological factors. Clinical management requires prompt hospitalization, aggressive supportive care, and empirical antibiotic therapy tailored to local and regional resistance patterns to ensure optimal outcomes.